Southeast Asia and the civil society gaze : scoping a contested concept in Cambodia and Vietnam - Waibel, Gabi; Ehlert, Judith; Feuer, Hart, 1983- (London: Routledge, 2014)
'As developing countries with recent histories of isolation and extreme poverty, followed by restoration and reform, both Cambodia and Vietnam have seen new opportunities and demands for non-state actors to engage in and manage the effects of rapid socio-economic transformation. This book examines how in both countries, civil society actors and the state manage their relationship to one another in an environment that is continuously shaped and (re)constructed by changing legislation, collaboration and negotiation, advocacy and protest, and social control. Further, it explores the countries' divergent experiences whilst also uncovering the underlying basis and drivers of civil society activity that are shared by Cambodia and Vietnam. Crucially, this book engages with the contested nature of what civil society is and means, by looking at contemporary discourses and manifestations of civil society in the two countries, national-level NGOs and agencies, and translocal networks that operate in a variety of sectors, such as gender, the environment and health'--
Includes bibliographical references and index.
Keywords: Civil society -- Cambodia; Civil society -- Vietnam; Non-governmental organizations -- Cambodia; Non-governmental organizations -- Vietnam; Social change -- Cambodia; Social change -- Vietnam